Perivascular macrophages in high-fat diet-induced hypothalamic inflammation - Natalia F. Mendes; Licio A. Velloso (Journal of Neuroinflammation, 2022)
Abstract Brain macrophages and microglia are centrally involved in immune surveillance of the central nervous system. Upon inflammatory stimuli, they become reactive and release key molecules to prevent further damage to the neuronal network. In the hypothalamic area, perivascular macrophages (PVMs) are the first line of host defence against pathogenic organisms, particles and/or substances from the blood. They are distributed throughout the circumventricular organ median eminence, wrapping endothelial cells from fenestrated portal capillaries and in the hypothalamic vascular network, where they are localised in the perivascular space of the blood–brain barrier (BBB). Some studies have indicated that PVMs from the hypothalamus increase the expression of inducible nitric oxide synthase and vascular endothelial growth factor upon feeding for a long time on a high-fat diet. This adaptive response contributes to the impairment of glucose uptake, facilitates BBB leakage and leads to increased lipid and inflammatory cell influx towards the hypothalamic parenchyma. Despite these early findings, there is still a lack of studies exploring the mechanisms by which PVMs contribute to the development of obesity-related hypothalamic dysfunction, particularly at the early stages when there is chemotaxis of peripheral myeloid cells into the mediobasal hypothalamus. Here, we reviewed the studies involving the ontogeny, hallmarks and main features of brain PVMs in vascular homeostasis, inflammation and neuroendocrine control. This review provides a framework for understanding the potential involvement of PVMs in diet-induced hypothalamic inflammation.